Integration of Life Skills (Intrapersonal Skills and Interpersonal Skills) Through Physical Education, Sports, and Health - Laeli Prastiwi, Catur Anggara; Rumini; Hermawan Pamot Raharjo (Journal of Physical Education and Sports, 2025)
This research was conducted based on the background of the problem at State Junior High School 3 Bantarsari, which is evidenced by the results of the questionnaire recapitulation. The percentage of student behavioral deviations at State Junior High School 3 Bantarsari falls into the high category, partly due to the influence of deviations at 34.7% and factors contributing to student behavioral deviations amounting to 88%, which are categorized as dominant. The researcher observed that students tend to have inconsistent Intrapersonal Skills and Interpersonal Skills, which affects physical education learning. Dominance occurs in the factors causing deviations in student behavior, namely individual and group factors. The purpose of this research is to analyze the influence of the integration between intrapersonal skills and interpersonal skills on physical education learning. This research is a quantitative study. The approach used is descriptive, correlational, and experimental, consisting of experimental group I: integration of intrapersonal skills; experimental group II: integration of intrapersonal skills and control group. The research data source is the eighth-grade students of State Junior High School 3 Bantarsari for the 2023/2024 academic year. Data collection techniques through observation, interviews, and questionnaires. Data analysis used paired and independent simple t-tests. This research produced significant data on the influence of Intrapersonal skills and Interpersonal skills on physical education learning. The study also found the development of an integration program through physical education learning, namely 1) Intrapersonal Skills (Goal Setting, Time Management, Leadership, Emotional Skills) and 2) Interpersonal Skills (Teamwork, Interpersonal Communication, Social Skills, and Problem Solving & Decision Making).(L. D. Cronin & Allen, 2017). The conclusion is that the application of the experimental group integrating intrapersonal skills and interpersonal skills through the paired sample t-test shows a difference in the average learning outcomes of students for the pre-post test experimental class with intrapersonal skills and interpersonal skills compared to the post-test control class. (non integrasi). In the independent sample t-test, the significance value was found to be < 0.005, concluding that Ho is rejected and Ha is accepted. Therefore, it can be concluded that there is a difference in the effect between PJOK learning integrated with interpersonal skills and intrapersonal skills and non-integration.